Climatic and environmental changes across the early Eocene climatic optimum at mid-Waipara River, Canterbury Basin, New Zealand - Crouch, E.M.; Shepherd, C.L.; Morgans, H.E.G.; Naafs, B.D.A.; Dallanave, E.; Phillips, A.; Hollis, C.J.; Pancost, R.D. (Earth-science reviews, 2020)
The Cretaceous–Paleogene marine sedimentary succession exposed in the banks of the middle reaches of the Waipara River (referred to as mid-Waipara), north Canterbury, New Zealand, has been the subject of several high-profile studies of Paleogene paleoclimate over the past decade. It is one of relatively few sections globally where a multi-proxy approach is possible due to the good preservation of microfossils and organic biomarkers. The Eocene section is also well dated by magnetostratigraphy and biostratigraphy based on planktic foraminifera, calcareous nannofossils and dinoflagellate cysts (dinocysts). Here, we build on this previous work and undertake a comprehensive analysis of paleontological and geochemical indicators of climatic and environmental changes through the early–middle Eocene part of the section, with particular focus on the early Eocene climatic optimum (EECO; 53.26–49.14 Ma). We correlate a 33.5m-thick interval with the EECO, based on biostratigraphy, magnetostratigraphy, TEX86-paleothermometry and bulk carbonate δ13C. Our new sea-surface temperature (SST) record based on TEX86 agrees with a previous lower resolution record based on TEX86 and planktic foraminiferal δ18O and Mg/Ca ratios. The EECO interval in this section extends from the upper part of the New Zealand Waipawan Stage to the Mangaorapan/Heretaungan Stage boundary at 49.27 Ma. The EECO onset is not exposed, but the termination is well constrained by a fall in SST and shift to more positive δ13C values. Six negative carbon isotope excursions (CIEs) are recognised within the EECO and are tentatively correlated with CIEs J/K, M, O, Q, T and C22nH4 in the global δ13C compilation. The CIEs are associated with warmer SSTs, indicating that they represent hyperthermals. The BAYSPAR TEX86 calibration indicates SST increased by as much as 12°C from the early Eocene (∼55 Ma) to the EECO, where SST peaked at 35°C. SST gradually declined from mid EECO (∼51 Ma) into the middle Eocene. The marked warming in the early EECO is associated with the highest abundance of warm-water taxa in calcareous nannofossil and dinocyst assemblages, the highest proportion of planktic foraminifera, and a coeval long-term shift to abundant angiosperm vegetation, primarily driven by a rise in Casuarinaceae. There is good agreement between TEX86 and marine microfossil-based proxies for temperature, providing confidence that both approaches are useful guides to past water temperature. Warm-water marine taxa are most abundant in the EECO but are not dominant. Comparison of the abundance of nannofossil warm-water taxa between mid-Waipara and a low-latitude site on Shatsky Rise suggests the latitudinal temperature gradient between mid- and low-latitudes in the EECO was greater than the TEX86 proxy implies. There is no clear evidence for enhanced sedimentation rates associated with the EECO, in contrast to evidence from the nearby Mead Stream section. Superabundant Homotryblium, a euryhaline dinocyst, in the early and middle EECO suggests elevated salinity and/or stratified surface waters, and there is no clear evidence of increased surface productivity associated with the EECO. Declining SST in the late EECO, ∼50 Ma, corresponds with an increase in cool-water taxa and terrigenous material. This article highlights the importance of combining well-calibrated paleontological and geochemical records to better constrain and understand past warm climate states.